I'm doing a past paper for one of my masters modules and I'm stuck on this


and I have no idea how to tackle such a thing. It's worth 30% of the exam so would be great if anyone here has any suggestions.



For Question (1), the payoff is given by \begin{align*} (S_T-S_{T_0})^+. \end{align*} Note that \begin{align*} E\left(e^{-r(T-T_0)} (S_T-S_{T_0})^+ \mid \mathscr{F}_{T_0}\right) &=S_{T_0}N(d_1)-e^{-r(T-T_0)}S_{T_0}N(d_2), \end{align*} where \begin{align*} d_1 &= \frac{(r+\frac{1}{2}\sigma^2)(T-T_0)}{\sigma \sqrt{T-T_0}}\\ &=(r+\frac{1}{2}\sigma^2)\sqrt{T-T_0}/\sigma, \end{align*} and \begin{align*} d_2 = d_1 - \sigma \sqrt{T-T_0}. \end{align*} The option price is then given by \begin{align*} C_0 &\equiv e^{-rT}E\left( (S_T-S_{T_0})^+ \right)\\ &=e^{-rT_0}E\left(E\left(e^{-r(T-T_0)} (S_T-S_{T_0})^+ \mid \mathscr{F}_{T_0}\right)\right)\\ &=e^{-rT_0}E\left(S_{T_0}N(d_1)-e^{-r(T-T_0)}S_{T_0}N(d_2) \right)\\ &=S_0 \big[N(d_1) - e^{-r(T-T_0)} N(d_2)\big].\tag{*} \end{align*}


For Question (2), note that \begin{align*} \max(S_T,\, S_{T_0}) = S_{T_0} + (S_T-S_{T_0})^+. \end{align*} Then, from (*), the contingent price is given by \begin{align*} P_0 &\equiv e^{-rT}E\left( S_{T_0} + (S_T-S_{T_0})^+ \right)\\ &=e^{-r(T-T_0)}S_0 + S_0 \big[N(d_1) - e^{-r(T-T_0)} N(d_2)\big]\\ &=S_0 \big[N(d_1) + e^{-r(T-T_0)} (1-N(d_2))\big]\\ &=S_0 \big[N(d_1) + e^{-r(T-T_0)} N(-d_2)\big]. \end{align*}


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.